2019
DOI: 10.1590/0034-7167-2018-0361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen in the development of retinopathy of prematurity

Abstract: Objective: to describe the influence of oxygen in retinopathy of prematurity (ROP) in premature newborns (PTNB) hospitalized in neonatal units of intensive care and undergoing ophthalmological follow-up procedures after hospital discharge. Method: retrospective cohort study, from January 2014 to June 2016, whose data collection totaled 181 charts. Descriptive and inferential statistical analysis. Results: when using oxygen (O2) in 148 PTNB (81.7%), both mask (n=141; 77.9%; p-value <0.001) and the tracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Por este motivo, no se puede concluir que la exposición a oxígeno suplementario y retinopatía de la prematuridad no estén asociados. Otros factores que pudieron influenciar en este resultado son el diseño del estudio y el hecho de incluir únicamente una unidad neonatal, más aún si se tiene en cuenta toda la evidencia previa al respecto 18,19 .…”
Section: Discussionunclassified
“…Por este motivo, no se puede concluir que la exposición a oxígeno suplementario y retinopatía de la prematuridad no estén asociados. Otros factores que pudieron influenciar en este resultado son el diseño del estudio y el hecho de incluir únicamente una unidad neonatal, más aún si se tiene en cuenta toda la evidencia previa al respecto 18,19 .…”
Section: Discussionunclassified
“…Both independent of and cumulatively with oxygen exposure, positive pressure ventilation is an important modifiable risk factor for severe ROP [ 41 , 42 , 43 , 44 , 45 ]. The duration of mechanical ventilation is a risk factor for ROP development [ 46 , 47 ], and several studies have confirmed prolonged mechanical ventilation as an independent risk factor for ROP [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Perinatal and Neonatal Risk Factorsmentioning
confidence: 99%
“…The duration of mechanical ventilation is a risk factor for ROP development [ 46 , 47 ], and several studies have confirmed prolonged mechanical ventilation as an independent risk factor for ROP [ 48 , 49 , 50 , 51 , 52 , 53 ]. Similarly, it has been established that long-term use of a CPAP is predictive of treatment-requiring or severe ROP [ 41 , 42 , 43 , 44 , 45 ]. There were no significant differences in the incidence of ROP between infants treated with bi-level positive airway pressure or CPAP [ 54 ].…”
Section: Perinatal and Neonatal Risk Factorsmentioning
confidence: 99%
“…3 The limit of viability has been between 22 and 28 weeks GA, however, it may change according to advances in technology and treatment of premature infants, since it depends on perinatal care of the delivery site and the ethical issues surrounding it. 7 Each service should establish its limit of viability, considering the ability to maintain an extreme PNs with quality of life. 4 To assess what determines neonatal mortality, it is important to know and monitor the factors that cause it, identify vulnerable groups, the different risk variables and the relationship with the progression to death, assisting in devices that bar this process since the prenatal period.…”
Section: Introductionmentioning
confidence: 99%